Торгівля товарами в керамічній тарі в IV ст. до н. е. (процедура порівняння статистичних показників імпорту) - Нємцев, С.О. (Археологія, 2017)
У статті доповнено методику порівняння кількісних показників надходження об’ємів товарів у античній керамічній тарі на основі кількох вибірок. Set of mathematic methods used for the comparison and evaluation of the informational content of import statistical indications from several sites is analysed. The conclusion is made that the most informative is the comparison of commodities supply indications not from separate exporting centres, but from groups of them. Three groups of exporting centres are determined for the 4th century BC: 1. The north-west area of the Aegean Sea; 2. The south-east area of the Aegean Sea; 3. The Black Sea. «Illustrative model», a new method of comparison the import statistical indicators for the sites with sets of amphorae materials of various capacity is proposed. Проанализировано набор математических методов, применимых для сравнения и оценки информативности статистических показателей импорта с нескольких памятников. Сделан вывод о наибольшей информативности сравнения показателей поступления товаров не отдельных центов экспортеров, а их групп. Выделены три группы центров экспортеров для IV в. до н. э.: 1. Северо-западная часть Эгейского моря; 2. Юго-восточная часть Эгейского моря; 3. Черное море. Предложен новый метод сравнения статистических показателей импорта для памятников с выборками амфорного материала разного объема — «иллюстративная модель».